Pengaruh Penerapan Permainan Ular Tangga Pada Model Pembelajaran Matematika Realistik (PMR) Terhadap Hasil Belajar Matematika Siswa SMP Negeri 2 Batuatas - Herlawan, Herlawan; Usa, Suwarni La; Sari, Fina (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2024)
This study aims to determine the effect of the application of snake and ladder games on Realistic Mathematics Learning (PMR) on the mathematics learning outcomes of SMP Negeri 2 Batuatas students. This research is a quantitative research using experimental methods. The total number of students in grade VII of SMP N 2 Batuatas with the number of parallel classes is 2 classes and the sample that can be taken in this study is 2 classes, namely class VII 1 and class VII 2 with a total of 48 students. Test instruments are used as a tool to collect research data. Independent test T-Test samples are used to analyze the data of research results. The conclusion of the data from the independent test of the T-Test sample obtained a value of ,t-calculate.= 4.292, this value is greater than ,t-table.=2.013. So that the value of ,t-calculate.> ,t-table. then Ho was rejected. In addition, the significance level of the analysis results was 0.000 < α = 0.05. So, the conclusion obtained from the problem is that there is a significant influence of the application of snake and ladder games on the Realistic Mathematics Learning Model on the mathematics learning outcomes of grade VII students of SMP Negeri 2 Batuatas.